On interculturality: knots, cobwebs and dissonances - Bonito Oliva, Rossella (Itinerari, 2023)
The evolution of anthropological thought in the relationship with different cultures and symbolic universes has shown the need to deal with the progressive enrichment of positions with respect to Otherness. Infinite Others have overlapped the Other, and the Other has spread in the plurality of discourses that cannot be traced back to the simple opposition between hegemonic culture and subordinate culture. This essay tries to traverse this complexity starting from two authors – Melville and Beatty, one white, the other black – to use the color of the skin as a key to understanding the symbolic nuances between a past that does not pass and a present cluttered with ghosts. A reflection on the prefix “inter” of the word interculturality aims to bring out the need for respect and attention to different times and forms of experience witnessed by the voices of the world and stories small and large, beyond the pretensions of the theory.